2015
DOI: 10.1113/jp271256
|View full text |Cite
|
Sign up to set email alerts
|

Gating modes of calcium‐activated chloride channels TMEM16A and TMEM16B

Abstract: Key pointsr Calcium-activated chloride channels TMEM16A and TMEM16B support important physiological processes such as fast block of polyspermy, fluid secretion, control of blood pressure and sensory transduction.r Given the physiological importance of TMEM16 channels, it is important to study how incoming stimuli activate these channels. Here we study how channels open and close and how the process of gating is regulated.r We show that TMEM16A and TMEM16B display fast and slow gating. These gating modes are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 59 publications
5
39
0
1
Order By: Relevance
“…Normalization was carried out using either G +120mV or G max to obtain G Norm (G/G max or G/ G +120mV ), which is proportional to the apparent open probability of the channel. We extracted the time constants by fitting the data to a mono or bi-exponential function of the form: y0+at/τitalic or y0+at/τf+bt/τswhere y 0 is the value of y when t→∞, t is the time, τ is a time constant, a and b are the contribution of fast and slow processes, and τ f and τ s are the fast and slow time constants [11], respectively. The dose-response curves were constructed using normalized currents; only patches with stable basal current obtained with 0 [Ca 2+ ] i were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normalization was carried out using either G +120mV or G max to obtain G Norm (G/G max or G/ G +120mV ), which is proportional to the apparent open probability of the channel. We extracted the time constants by fitting the data to a mono or bi-exponential function of the form: y0+at/τitalic or y0+at/τf+bt/τswhere y 0 is the value of y when t→∞, t is the time, τ is a time constant, a and b are the contribution of fast and slow processes, and τ f and τ s are the fast and slow time constants [11], respectively. The dose-response curves were constructed using normalized currents; only patches with stable basal current obtained with 0 [Ca 2+ ] i were used.…”
Section: Methodsmentioning
confidence: 99%
“…This V m -dependence is explained by a voltage-dependent Ca 2+ dissociation [49]. We have shown that TMEM16A and TMEM16B exhibit fast and slow gating modes [11]. Both modes depend on intracellular Ca 2+ , membrane voltage (V m ) and the extracellular Cl − concentration ([Cl − ] o ).…”
Section: Introductionmentioning
confidence: 99%
“…The basis for this effect is currently unknown since the location of the mutation is remote from the Ca 2+ binding site. Still, it is noteworthy that this residue is located in proximity to a stretch of amino acids that in TMEM16A was identified to influence Ca 2+ sensitivity [55,58,59]. The major question of how Ca 2+ ions activate scrambling is currently unknown.…”
Section: Lipid Transfer Ratesmentioning
confidence: 99%
“…20 The kinetics of TMEM16A and TMEM16B Cl − conductance are complex, with distinct fast and slow gating mechanisms, regulated by membrane voltage and Cl − concentration. 21 Biophysical experiments suggest TMEM16A is present in membranes as a homodimer, 22, 23 with the dimerization domain located in the N-terminal sequence. 24 Recently, the C-terminal region of TMEM16A was modified to produce a constitutively active channel, providing a strategy to design TMEM16A activators.…”
Section: Introductionmentioning
confidence: 99%
“…26 Using the nhTMEM16 structure, two homology models of TMEM16A suggest it contains ten transmembrane helical segments, 21, 25 revising earlier eight helix structural models.…”
Section: Introductionmentioning
confidence: 99%